THE METHODOLOGY OF IMPROVING STUDENTS’ SOCIAL COMPETENCIES RELATED TO FOLK CRAFTS IN THE PROCESS OF PRACTICAL TRAINING - Esanova Sarvinoz Uktamovna (The Conference Hub, 2025)
This article examines the methodology for improving students’ social competencies related to folk crafts during practical training sessions. The study emphasizes the importance of integrating national cultural heritage, traditional craftsmanship, and creative activities into the educational process. By involving students in hands-on craftsmanship and collaborative projects, practical training not only enhances their professional skills but also develops social interaction, communication, responsibility, leadership, and cultural identity. The research highlights effective pedagogical approaches that support the formation of socially active, creative, and culturally aware individuals capable of preserving and promoting folk crafts in modern society.
Keywords: folk crafts, social competencies, practical training, cultural heritage, creative activity, pedagogical methodology, communication skills, national traditions, professional skills, educational process.